COVID- 19 Pandemic and The Precarity of Life: Rethinking a Pedagogy of Compassion so That The People of This Earth May Live - Bekithemba Dube; Nathan Moyo (JETL (Journal of Education, Teaching and Learning), 2021)
This article interrogates humanity’s individual and collective responses to the outbreak of the COVID-19 pandemic, which has been unprecedented in its deadly, unstoppable spread. Widespread illness and deaths across the world as a result of COVID- 19 have invoked grim reminders of our mutual vulnerability The article reimagines a pedagogy of compassion informed by the principles of Ubuntu. In the conclusion, the article reflects on how the pandemic may have brought out the best in humanity, as our mutual vulnerability has taught us to care for each other.